2010
DOI: 10.3732/ajb.1000081
|View full text |Cite
|
Sign up to set email alerts
|

Polystichum munitum (Dryopteridaceae) varies geographically in its capacity to absorb fog water by foliar uptake within the redwood forest ecosystem

Abstract: This study shows the first evidence that foliar uptake varies within species at the landscape scale. Our findings suggest that the P. munitum at the southern tip of the redwood ecosystem may suffer most from low summertime water availability because it had no potential to acquire fog as an aboveground water subsidy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 49 publications
3
47
0
Order By: Relevance
“…This is a topic of a growing interest for plant ecophysiology (Helliker & Griffiths 2007, Limm & Dawson 2010, Berry et al 2014, Rosado & Holder 2013, Berry et al 2013, Helliker 2014 as they may play an important ecophysiological role.…”
Section: Discussionmentioning
confidence: 99%
“…This is a topic of a growing interest for plant ecophysiology (Helliker & Griffiths 2007, Limm & Dawson 2010, Berry et al 2014, Rosado & Holder 2013, Berry et al 2013, Helliker 2014 as they may play an important ecophysiological role.…”
Section: Discussionmentioning
confidence: 99%
“…Burgess and Dawson, 2004;Oliveira et al, 2005;Breshears et al, 2008;Limm et al, 2009;Simonin et al, 2009;Limm and Dawson, 2010;Berry et al, 2013Berry et al, , 2014Gotsch et al, 2014). Holm oak is a species native to Mediterranean-type climates where summer drought is imposed by a combination of high temperatures and low precipitation.…”
Section: Leaf Water Uptake and Ecophysiological Implicationsmentioning
confidence: 99%
“…Such surface features together with their chemical composition (Khayet and Fernández, 2012) may lead to a high degree of roughness and hydrophobicity (Koch and Barthlott, 2009;Konrad et al, 2012). The interactions of plant surfaces with water have been addressed in some investigations (Brewer et al, 1991;Brewer and Smith, 1997;Pandey and Nagar, 2003;Hanba et al, 2004;Dietz et al, 2007;Holder, 2007aHolder, , 2007bFernández et al, 2011Fernández et al, , 2014Roth-Nebelsick et al, 2012;Wen et al, 2012;Urrego-Pereira et al, 2013) and are a topic of growing interest for plant ecophysiology (Helliker and Griffiths, 2007;Aryal and Neuner, 2010;Limm and Dawson, 2010;Kim and Lee, 2011;Berry and Smith, 2012;Berry et al, 2013;Rosado and Holder, 2013;Helliker, 2014). On the other hand, the mechanisms of foliar uptake of water and solutes by plant surfaces are still not fully understood (Fernández and Eichert, 2009;Burkhardt and Hunsche, 2013), but they may play an important ecophysiological role (Limm et al, 2009;Johnstone and Dawson, 2010;Adamec, 2013;Berry et al, 2014).…”
mentioning
confidence: 99%
“…Within California, redwoods inhabit a narrow strip of land from approximately 42 to 35.8 degrees N latitude and a zone fewer than 40 km from the ocean, a region known for its summer fog and winter rain (Noss 2000). Research on soil water and understory plants (Dawson 1998, Limm and Dawson 2010, Limm et al 2009) and trees (Ambrose et al 2009, Burgess and Dawson 2004, Ewing et al 2009, Ingraham and Matthews 1995, Limm et al 2009, Simonin et al 2009) has shown that fog water is taken up directly into plant leaves within fog-enshrouded coastal California forests.…”
Section: Introductionmentioning
confidence: 99%